Voluntary simplicity: A literature review and research agenda. (14th October 2020) - Rebouças, Raquel; Soares, Ana Maria
Abstract: Voluntary simplicity (VS) is a lifestyle focused on seeking a simple life by reducing consumption and other practices. This systematic literature review aims to analyse and critically discuss the state of the art of VS. This review provides a categorization scheme of VS and analyses: the number of studies and year of publication; journals, number of citations and research areas; study location; VS definitions; types of studies; and research methods. By providing a map of existing research, the paper contributes to the clarification of the VS construct and to the assessment, synthesis and identification of research gaps, and opportunities for further research. VS implications for theory, practice and policy are discussed within the context of consumption/anti‐consumption.